PENGARUH AKTIVITAS BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 21 AMBON - Sofyan, Abdul; Ratumanan, Tanwey Gerson (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2018)
This study is ex-post facto studythat is causal in nature in order to measure the direct and indirect effects of learning and independence of learning activities on learning outcomes. The study was conducted on 151 students of SMP Negeri 21 Ambon. Data was collected using observation, questionnaires, and tests. Data analysis used descriptive statistics and Structural Equation Model (SEM). From this study the results were obtained: (1) There was an effect of learning activities on student self-learning directly by , including the medium category; (2) There is an influence of learning activities on students' mathematics learning outcomes directly by , including the medium category; (3) There is an effect of learning independence on students' mathematics learning outcomes directly by , including the low category; (4) There is an influence of learning activities on student mathematics learning outcomes indirectly through learning independence by , including low categories; (5) Total effect of learning activities to students' mathematics learning outcomes either directly or indirectly through independent learning  including the big categories